2020
DOI: 10.21470/1678-9741-2019-0274
|View full text |Cite
|
Sign up to set email alerts
|

The Validation of the ATRIA and CHA2DS2-Vasc Scores in Predicting Atrial Fibrillation after Coronary Artery Bypass Surgery

Abstract: Objective The aim of this study was to evaluate the value of CHA 2 DS 2 -VASc and Anticoagulation and Risk Factors in Atrial Fibrillation (ATRIA) risk scores for prediction of postoperative atrial fibrillation (AF) development in patients undergoing coronary artery bypass grafting (CABG) operation. Methods The population of this observational study consisted of 370 patients undergoing CABG operation. CHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
(34 reference statements)
0
6
0
4
Order By: Relevance
“…Postoperative atrial fibrillation (PoAF) is extremely important because it causes poor general condition in patients, increases treatment costs by prolonging hospitalization periods and causes morbid consequences such as cerebrovascular events. In the literature, various scoring systems have been investigated to predict PoAF [ 11 ]. With this current prospectively designed study, we found that HATCH score and WHR are independent predictors of PoAF after CABG operations with CPB (WHR: Odds ratio: 1.068, Confidence interval: 1.032–1.105, p < 0.001, HATCH score: Odds ratio: 2.590, Confidence interval: 1.850–3.625, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative atrial fibrillation (PoAF) is extremely important because it causes poor general condition in patients, increases treatment costs by prolonging hospitalization periods and causes morbid consequences such as cerebrovascular events. In the literature, various scoring systems have been investigated to predict PoAF [ 11 ]. With this current prospectively designed study, we found that HATCH score and WHR are independent predictors of PoAF after CABG operations with CPB (WHR: Odds ratio: 1.068, Confidence interval: 1.032–1.105, p < 0.001, HATCH score: Odds ratio: 2.590, Confidence interval: 1.850–3.625, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…При этом летальность пациентов с гемодинамически-значимыми аритмиями составила 35,0%, тогда как в исследованиях сторонних авторов данный показатель варьирует от 3,6% [20] до 9,0% [16]. Данное различие, вероятно, является следствием того, что оценивались близкие, но не тождественные явления: в настоящем исследовании -«впервые возникшие гемодинамически значимые аритмии», в цитируемых публикациях -«впервые выявленная фибрилляция предсердий».…”
Section: Discussionunclassified
“…Ранее сообщалось о достаточной значимости обсуждаемых шкал в плане прогнозирования фибрилляции предсердий [16,17,19,20]. Выше уже было предложено возможное объяснение причин несоответствия результатов выполненного исследования и данных литературы:…”
Section: Discussionunclassified
See 2 more Smart Citations